2017
DOI: 10.20937/rica.2017.33.04.05
|View full text |Cite
|
Sign up to set email alerts
|

USO DE UN REACTOR DE PLACA PLANA (TiO2/VIDRIO) PARA LA DEGRADACIÓN DE 2,5-DICLOROFENOL POR FOTOCATÁLISIS SOLAR

Abstract: Palabras clave: fotocatálisis heterogénea, método sol-gel, dinámica del reactor RESUMEN La degradación de compuestos orgánicos no biodegradables presentes en aguas residuales es un punto central de la fotocatálisis solar debido a su alta eficiencia y aceptables costos de operación. Se estudió la degradación de 2,5-diclorofenol (2,5-DCF) en solución acuosa con concentración inicial variable (C0 ≤ 98 mg/L), por fotólisis y fotocatálisis solar con un reactor de placa plana (1 m 2 ) y vidrio impregnado con TiO2 si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…The absorbance spectra obtained from the photocatalysts via UV-Vis spectrophotometry with integration sphere, were treated by the modified Kubelka-Munk method, obtaining the graphic representation [F(R)hυ] 2 againsthυ where, when projecting the linear part of the curve to the energy axis, allowed the determination of the magnitude of the band opening of semiconductor energy or band-gap needed to produce the energy gap that promotes the formation of the •OH radicals necessary for photocatalysis [24]. Figures 3 and 4 show the graphs composed of the absorbance spectrum and the band-gap calculation for C1-TiO 2 and TiO 2 P25 made with Origin Pro 8 software (OriginLab, Northampton, MA, USA), these being lower than the values shown in the semiconductors obtained by the sol-gel method with titanium tetrabutoxide (TBT) and titanium tetraisopropoxide (TIPT) as precursors, which have values of 3.40 eV and 3.38 eV respectively [14,25]. These results indicate a faster activation of the photocatalysts TiO 2 P25 and C1-TiO 2 to the exposure to high radiation emission, in this case, solar energy.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…The absorbance spectra obtained from the photocatalysts via UV-Vis spectrophotometry with integration sphere, were treated by the modified Kubelka-Munk method, obtaining the graphic representation [F(R)hυ] 2 againsthυ where, when projecting the linear part of the curve to the energy axis, allowed the determination of the magnitude of the band opening of semiconductor energy or band-gap needed to produce the energy gap that promotes the formation of the •OH radicals necessary for photocatalysis [24]. Figures 3 and 4 show the graphs composed of the absorbance spectrum and the band-gap calculation for C1-TiO 2 and TiO 2 P25 made with Origin Pro 8 software (OriginLab, Northampton, MA, USA), these being lower than the values shown in the semiconductors obtained by the sol-gel method with titanium tetrabutoxide (TBT) and titanium tetraisopropoxide (TIPT) as precursors, which have values of 3.40 eV and 3.38 eV respectively [14,25]. These results indicate a faster activation of the photocatalysts TiO 2 P25 and C1-TiO 2 to the exposure to high radiation emission, in this case, solar energy.…”
Section: Introductionmentioning
confidence: 92%
“…Two solar reactors with contact areas of 1/10 m 2 (reactor 1) and 1 m 2 (reactor 2) were used. Such reactors, shown in Figure 7, are formed by a metal base that supports the rest of the system with an inclination of 20 • , which is close to the latitude of Durango City, Mexico (24 • 01'37" N), so that the solar radiation uptake is maximized [14]. On the base, an acrylic container is supported within which frosted glass plates are placed.…”
Section: Photocatalytic Reactorsmentioning
confidence: 99%
See 1 more Smart Citation
“…1b). TiO 2 photocatalyst was characterized in its microstructural forms by X-ray diffraction (XRD), and its band gap determined by UV-Vis-NIR spectrophotometry, by the Kubelka-Munk method, under previously reported operating conditions (Morones- Esquivel et al, 2017). The glass plate has a contact area of 1 m 2 (1.25 m x 0.80 m) and was adjusted to two different experimental angles (20°and 26°) with respect to the horizontal, close to the latitude of Durango City, Mexico (24°01' 37" N), with the purpose of capturing the greatest amount of solar energy (Blanco, 2005).…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, and taking into account the reactor dynamics Hao, 1991 andWolfrum and Turchi, 1992;Moctezuma et al, 2016), as well as considering several nano-structural parameters (particle size, specific surface area and crystalline phase of the photocatalyst, TiO 2 , among others), our research group reported the degradation of 2,5-DCP by photocatalysis in long reaction times, using a TFSR, with degradation percentages of up to 98% and demonstrating that the order of reaction, with respect to the concentration of 2,5-DCP, is determined in the interval of both orders (zero and one) and that throughout this transition of the order of reaction, changes in reaction rate are proportional to a magnitude ranging from 1 − exp(−K 1 Θ 2 ) to K 1 (Morones- Esquivel et al, 2017).…”
Section: Introductionmentioning
confidence: 94%